Quality of Refrigerated Tilapia (Oreochromis niloticus) Slices under Vacuum and Modified Atmosphere Packaging - Karim, Md. Abdul; Rahman, Masudur; Alice, Esmout Jahan; Amanullah, Md.; Hossain, Md. Akhtar; Islam, Md. Tariqul (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
In order to develop a proper packaging system for sliced tilapia fish (Oreochromis niloticus), the biochemical and microbiological qualities under control (unsealed package), vacuum package and modified atmosphere packaging with 50% CO2/50% N2 (MAP-1)  and 50% CO2/50% O2 (MAP-2)  were evaluated every three days during 18 days of chilled storage (4±1°C). The pH value was not significantly different (p 0.05) by treatments until day 9, but significantly lower values (p 0.05) were observed on day 12 of the storage in all treated samples compared to the control. The total volatile base nitrogen (TVB-N) value progressively increased, but not significantly different (p 0.05) in all treatments during the entire storage period. The thiobarbituric acid reactive substances (TBARS) amounts were significantly lower (p 0.05) on day 12 in the vacuum and MAP-1 samples compared to the control sample, and were significantly higher (p 0.05) on day 6, 9, and 12 of the storage period in MAP-2 samples compared to the control, vacuum and MAP-1 samples. The amounts of pH, TVB-N, and TBARS in all samples did not exceed the acceptable limit in almost the entire storage. The total viable count (TVC) progressively increased with storage time. Nevertheless, TVC values were lower (p 0.05) on day 6, 9, and 12 of the storage periods in all treatments compared to the control. The TVCs exceeded the acceptable limit (7 log CFU/g) on days 6-9 for control, 9-12 for vacuum, day 12 for MAP-2, and 15 for MAP-1 sample during the storage period. Therefore, the MAP has shown promising results for shelf life extension that can be practiced to display the fishery products with prolonged shelf life.